Imunisasi Ikan Jambal Siam dengan Vaksin Ichthyophthirius multifiliis - Syawal, Henni; Ikhwan Siregar, Yusni (Jurnal Veteriner; Vol 11 No 3 (2010), 2010)
An experiment on the immunization of Jambal Siam ( Pangasius hypophthalmus) withIchthyophthirius multifiliis vaccine was conducted in the Laboratorium of Parasitic and Fish Diseases,Faculty Fisheries and Marine Science of Riau University, and Laboratorium of Fish Health of FacultyFisheries and Marine Science, IPB. The objective of the study was to enhance immune system of the fishfry on the ichthyophthiriasis diseases. The vaccine was prepared by prolonged treatment of theron in waterbath of 47°C for 30 minutes. The vaccine was administrated to fish by immersion in aquaria. A completelyrandomized design (CRD) in factorial pattern (3 X 3 X 3) was carried out with dose and time as factors.Doses of treatment and time of immersion were of 1 ml/L, 2 ml/L and 3 ml/L as well as 15, 30 and 45minutes of treatment time respectively. To evaluate the effectiveness of vaccine in fish, a challenge test tofish was done at day 15 with theron 90.000 cell/ aquaria until rearing day 25 after vaccination. It revealedthat the best performance (p<0.5) were of dose 3 ml/L and time treatment of 15 minutes in that survivalrate of fish was 100% followed by dose 3 ml/L with time 45 minutes (63,3%). The total erythrocyte count,hematocrit level and hemoglobin of tested fish were fluctuated. The water quality were recorded including;dissolved oxygen range from 3,74 - 4,98 ppm; temperature 25 - 30°C and acidity of 4 - 6, quality were ofnormal range for fish. The optimal vaccine dose is 3 ml/l with 15 minute immersion.
Keywords: Ichthyophthyirius multifiliis, Immunization, Jambal siam, Vaccine